Pharmacognostic studies on ethno-medicinal plant Aerva lanata (l.) Juss - UJWALA G.MALODE (International Journal of Pharma and Bio Sciences, 2017)
Aerva lanata (L.) Juss belonging to family Amaranthaceae is used as the drug source by virtue of it’s medicinal properties like diuretic, demulcent and anthelmintic. It is also used as painkiller in the treatment of headache and for cough, cutaneous infections, in white urine, diarrhoea, cholera, dysentery and in kidney stone. The internal structure of root, stem and leaves were studied. Root and stem shows rings of secondary vascular bundles. Calcium oxalate crystals are present in the cortex and pith region of the stem and mesophyll and midrib of leaf. The genus Aerva lanata is characterized by well developed, multicellular, uniseriate, unbranched trichomes which are composed of few short basal cells with yellow walls and several longer cells. Presence of small knobs and papillae on walls is characteristic feature of hair. Phytochemical analysis showed the presence of carbohydrates, proteins, amino acids, glycosides, flavonoids, alkaloids, tannins and phenolics. Medicinal significance of this plant is due to Presence of these secondary metabolites.